Electronic Word-of-Mouth Turis Muslim Mengenai Pariwisata Halal di Lombok, Nusa Tenggara Barat, Indonesia - Dhyayi Warapsari; Effy Zalfiana Rusfian (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Electronic word-of-mouth (eWOM) communication from tourists that have visited a destination can be used as promotional media for that destination, including in the halal tourism context. Understanding the drivers of Muslim tourist’s eWOM is necessary to be able to use eWOM as a means of promoting halal tourism in Indonesia. This research aims to analyze the direct effects of Islamic religiosity, perceived values, and destination satisfaction on eWOM; the mediating effects of destination satisfaction on the link between Islamic religiosity, perceived value, and eWOM; the serial mediating effect of perceived Islamic values and destination satisfaction on the link between Islamic religiosity and eWOM; and comparing the effects of perceived value dimensions, i.e., quality, price, emotional, social, different experience, novelty, safety, location, physical attributes, and nonphysical attributes, on eWOM. This research used the positivism paradigm and quantitative method. The population was Indonesian Muslim tourists who have visited halal tourism destination in Lombok, West Nusa Tenggara. Purposive and snowball sampling methods were used to select samples. The data were collected from 332 respondents via an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) method. This research found that only perceived social value that has a significant effect on eWOM, while Islamic religiosity, the other dimensions of perceived value, and destination satisfaction are not the direct and indirect drivers of eWOM. The difference in the significance of the effects of those factors can be associated with the origin and age of the respondents, as well as the location of the destination.